A reappraisal of the hermit crab genera Catapagurus A. Milne-Edwards and Hemipagurus Smith (Crustacea: Decapoda: Anomura: Paguridae), with the description of a new species - Mclaughlin, Patsy A. (Zootaxa, 2004)
The discovery of a new species from the waters of eastern Australia and New Caledonia has required a reassessment of the merit of the reinstatement of the hermit crab genus Hemipagurus Smith, 1881. Reappraisal of all characters ascribed to both Catapagurus A. Milne-Edwards, 1880 and Hemipagurus, in light of the attributes of Catapagurus franklinae n. sp., has demonstrated unequivocally that there is no justification for the resurrection of Hemipagurus. Consequently, this genus is once again relegated to the status of junior synonym of Catapagurus, and all of the species reassigned to or recently described in the genus Hemipagurus are returned to, or transferred to, Catapagurus. Catapagurus spinicarpus de Saint Laurent & McLaughlin, 2000, and C. danida McLaughlin, 2002, two species not considered in the recent revision, are compared to their closest congeners, as is the new species.